The multivariate statistics applied to the characterization of backyard poultry production in Cienfuegos province - Casanovas Cos?o, E.; Bernal, Yamilka; Lon Wo, Esmeralda (Cuban Journal of Agricultural Science, 2014)
The multifactorial characterization of the backyard poultry production systems was conducted in the eight municipalities of Cienfuegos province. One hundred seventy five rearing backyards randomly selected were used, for a reliability of 95 %, proportionally distributed in each municipality. In a transversal observational design with surveys, 17 social, 32 husbandry and 27 epizootiolocal variables were identified. The people inquired are described with an average age of 45 years, male sex predominating (62.90 %) and finished high education (66.9 %). Four husbandry components and five epizootiological ones characterizing the backyard poultry production in Cienfuegos province were identified, with variance explained from 72.90 and 67.22 %, respectively. The components of higher variability for the husbandry and epizootiological were: elements of the productivity, feeding oportunities, bioprotection and ectoparasitosis that explained 50.6 and 40.5% of the total variances. The indicators created: husbandry and epizootiological capacity showed low performance, without differences between the municipalities. Considering the methodology used and the results for strategies in the development of alternative of backyard poultry activity is recommended. Key words: backyard poultry rearing, alternative, principal components, epizootiology, husbandry.